Universal Model of Lost Profits Calculation - Butkevičius, Rimas (Ekonomika, 2020)
Consequential (or indirect) losses in the form of lost profits are usually suffered and claimed in civil cases of breaches of supply or service contracts, unfair competition, bankruptcy cases, and other instances where a defendant’s wrongful actions cause lost profits to the plaintiff’s performance.In litigation practice, we see a quite different approach, when the lost profits are calculated as gross margin less income tax, and in others – by multiplying the lost revenues by the company’s net profit ratio.Methods of indirect loss calculation applied do not consider the cost structure of the plaintiff and the impact of the variation of variable and fixed costs to the lost profit calculation before and after the wrongful action of the defendant. In case lost revenues would have been received, fixed costs would remain the same, while variable (incremental) costs, which were avoided, would be generated to receive lost revenues.Based on the international experience and practices, this article provides for a Universal Model of lost profits calculation as well as a mathematical formula of the method.
Keywords: damage; indirect loss; lost revenues; incremental costs